Trends and regional variations in chronic diseases and their risk factors in China: an observational study based on National Health Service Surveys - Long Xue; Min Cai; Qinqin Liu; Xiaohua Ying; Shiyong Wu (BMC, 2023)
Abstract Background Over the past 25 years, the spectrum of diseases in China has rapidly changed from infectious to non-communicable diseases (NCDs). This study aimed to identify the prevalence of chronic diseases over the past 25 years in China and estimate the trends and changes in risk factors related to NCDs. Methods We conducted a descriptive analysis based on the National Health Service Survey (NHSS) from 1993 to 2018. The survey year (in parentheses) and its respective number of respondents were (1993) 215,163; (1998) 216,101; (2003) 193,689; (2008) 177,501; (2013) 273,688; and (2018) 256,304. In each survey, approximately half the participants were male. In addition, we estimated the trends in the prevalence and risk factors of NCDs from 1993 to 2018 and described their coefficient of variation in the provisions. Results The prevalence of NCDs has risen rapidly, from 17.0% in 1993 to 34.3% 2018. Hypertension and diabetes were the two main NCDs accounting for 53.3% in 2018. Similarly, the prevalence of hypertension and diabetes have also increased rapidly, increasing 15.1 and 27.0 times respectively from 1993 to 2018. Moreover, from 1993 to 2018, the proportion of smoking decreased from 32.0% to 24.7%, and the proportion of drinking and physical activity increased from 18.4% and 8.0% to 27.6% and 49.9%, respectively. The proportion of obesity increased from 5.4% in 2013 to 9.5% in 2018. The prevalence of NCDs in rural areas (35.2%) in 2018 was slightly higher than that in urban areas (33.5%). Changes in the prevalence of NCDs in rural were larger than those in urban. However, from 2013 to 2018, the provincial gaps for these metrics narrowed, except for that of smoking (Coefficient of Variation from 0.14 to 0.16). Conclusions The prevalence of NCDs increased rapidly in China and was similar in urban and rural areas in 2018. Two key risk factors (drinking and obesity) increased in prevalence, while the other two (smoking and physical inactivity) decreased. These results indicate that China is facing considerable challenges in curbing chronic diseases to achieve the United Nations Sustainable Development Goals or the Healthy China 2030 goals. The government should take more active measures to change unhealthy lifestyles, improve efficiency in risk factor management, and pay more attention and allocate more health resources to rural areas.